The Quality of Bus Rapid Transit (BRT) Shelter Services of Mangkang-Penggaron Route in CBD Semarang - Mahardhini, Putri; Rahdriawan, Mardwi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
The Government of Semarang have sought to develop a mass transportation system using the concept of Bus Rapid Transit (BRT) in Mangkangâ€Penggaron corridor. In order to effectively facilitate the movement of city dwellers, the BRT system required the provision of functioning shelters along the corridor. There is a need to optimize the function of the shelters including the integration to other modes of transportation and to the activities of the Central Business District (CBD), ensuring optimum performance of the whole BRT system. This study determined and evaluated the quality of BRT shelter services in Semarang based on user perception. The study employed analysis regarding the fulfillment of criteria for quality of services including waiting time, convenience, service reliability, distance, and BRT shelter clerk services. The analysisprocesses concluded that the current BRT shelter services were in fact less than ideal. The study found lack of maintenance and the need for improvement of services at rush hour.